The Impact of Celebrity Endorsements and Digital Marketing on Purchase Intentions Among Tokopedia Users: A Study of Students - Rismayani, Rismayani; Fadli, Mashur (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This research aims to find out whether there is an influence of the use of celebrity endorsers and advertisements through digital marketing on the buying interest of Tokoedia users and to find out whether student objects are able to influence purchases on Tokopedia with the presence of celebrity endorsers and advertisements displayed by Tokopedia. The research method used is a quantitative method and uses secondary and primary data. Primary data was obtained from respondents who were collected through a questionnaire consisting of 30 questions. The sample consisted of 97 active students from the Faculty of Economics and Business, Riau University, Tokopedia users with a population of 3855 students and used a purposive sampling technique. The data analysis technique for this research uses PLS-SEM versi 4. The results of the research show, (1) There is a positive and significant influence of celebrity endorsers on the buying interest of Tokopedia users among students at the Faculty of Economics and Business, Universitas Riau, (2) There is a positive and significant influence of advertising on users' buying interest Tokopedia among students at the Faculty of Economics and Business, Universitas Riau, (3) There is a positive and significant influence of celebrity endorsers on the digital marketing of Tokopedia users among students at the Faculty of Economics and Business, Universitas Riau, (4) There is a positive and significant influence of advertising on the digital marketing of Tokopedia users among students. Faculty of Economics and Business, Universitas Riau, (5) There is a positive and significant influence of digital marketing on the buying interest of Tokopedia users among students of the Faculty of Economics and Business, Universitas Riau, (6) celebrity endorsers on buying interest through digital marketing do not have a positive influence on the use of Tokopedia in students at the Faculty of Economics and Business, Universitas Riau, and (7) There are advertisements that have a positive and significant effect on buying interest through digital marketing of Tokopedia users among students at the Faculty of Economics and Business, Universitas Riau.